Epstein-Barr Virus-Related Hemophagocytic Lymphohistiocytosis: Hematologic Emergency in the Critical Care Setting. (10th February 2015) - Hashemi-Sadraei, Neda; Vejpongsa, Pimprapa; Baljevic, Muhamed; Chen, Lei; Idowu, Modupe
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare and potential life-threatening clinical syndrome that results from uncontrolled activation of the immune system. Secondary HLH, more commonly observed in adult patients, is seen in the context of underlying triggering conditions. Epstein-Barr virus (EBV) has been recognized as the leading infectious cause and is associated with a poor outcome. As clinical and laboratory features of HLH could overlap with septic shock syndrome in most patients, the diagnosis of HLH, especially in adults, is the most challenging aspect of the disease that results in delayed recognition and treatment of rapidly progressive multiorgan system failure. We report a case of Hemophagocytic lymphohistiocytosis in a patient who presented with signs of septic shock syndrome and we review the literature on the topic.